Influence of Lithiophilic Substrates on Lithium Metal Batteries at Low Temperature. Issue 12 (1st December 2022) - Kim, Kangwoon; Li, Mingqian; Kim, Taehee; Yin, Yijie; Cai, Guorui; Holoubek, John; Chen, Zheng
Abstract : Lithium metal batteries (LMBs) are an emerging technology that promises to provide high energy density that could compensate for the energy loss of lithium-ion batteries (LIBs) at low temperatures. However, tip-driven growth during lithium deposition remains a problem for LMBs at low temperatures, which should be mitigated for improved cyclability and safety. Tailoring lithium metal nucleation with lithiophilic substrates has shown effectiveness in improving cycling performance at room temperature, but the investigation at low temperatures is limited. For this work, promoting homogeneous lithium nucleation by implementing a lithiophilic substrate, lithiated graphite (LiC6 ), the adverse effects of low temperature on Li cycling were alleviated in a model electrolyte. This lithiated graphite substrate provided 4.2% and 4.5% higher measured coulombic efficiency for Li cycling compared to copper at −20 °C and −40 °C, respectively, which demonstrated higher specific capacity and improved cyclability for 2× excess Li||Ni0.6 M0.2 C0.2 O2 full cells.